Distinct raindrop size distribution microphysical mechanisms of frontal and warm-sector heavy rainfall in Coastal Southeast China - Mingrui Guo; Wen Lin; Jingjing Lv; Chenglong Gong; Qing Duan; Jingxi Sun; Pengcheng Lin; Chunsong Lu; Yiqi Chen (Atmospheric Research, 2026)

Life history strategy composition of fishes in the Yangtze River Basin and their response to the Ten-Year Fishing Ban - Lan Zhu; Dan Yu; Pengcheng Lin; Fei Liu; Tao Chang; Xin Gao; Mingzheng Li; Huanzhang Liu (Reviews in Fish Biology and Fisheries, 2026)

Quasi-static cyclic tests of innovative prefabricated CFST bridge piers with replaceable components - Zhehan Cai; Jianguang Lin; Ying Sun; Pengcheng Xu; Zhiyu Lan; Kaiqi Lin; Weidong Zhuo (Engineering Structures, 2026)

Piezoelectric-photocatalysis assisted chemical mechanical polishing: A cost-effective and efficient approach to atomic-scale processing of RS-SiC surfaces - Xingwang Xu; Jiayi Liu; Bin Lin; Tianyi Sui; Jinming Li; Bingrui Lv; Pengcheng Zhao; Hetian Hou; Cong Chen; Hualong Zhang; Yuhao Zhang; Jinhua Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

Fe3+-PMS-assisted oxidative pre-modification of reed straw enables ultramicroporous carbon nanosheets for efficient CO2 capture and solar-driven regeneration - Fengming Chen; Lantao Gu; Lin Huang; Pengcheng Guo; Xiancheng Ma; Qian Lin (Chemical Engineering Journal, 2026)

Defect-reconfigured nanosheet-like porous carbon via in situ oxalate activation of lignosulfonate for high-performance biomass-based supercapacitors - Fengming Chen; Pengcheng Guo; Zheng Zeng; Liqing Li; Qian Lin; Xiancheng Ma (Chemical Engineering Journal, 2026)

Strong metal-support interaction boosts the activity and stability of CeO2 supported Pt nanocatalysts for dichloromethane oxidation - Xiuguan Liu; Maosen Xu; Qi Lin; Pengcheng Yu; Yuanhao Ye; Hongli Liu; Deyun Ma (Environmental Research, 2026)

Morphotectonic characteristics of the Xiongpo anticline in the southwestern Sichuan Basin, China: Implications for active folding mechanisms - Xiaohan Yin; Gang Rao; Lin Gao; Yan Wu; Yaqi Zhong; Pengcheng Tang; Renfu Wang (Geomorphology, 2026)

Alpha-2-macroglobulin attenuates glucocorticoid-induced osteonecrosis of the femoral head by enhancing osteogenesis and antioxidant defense via the Akt/Nrf2 signaling pathway - Qingjian He; Xin Zheng; Boyun Huang; Xianjie Xie; Manying Lin; Pengcheng Lin; He Chen; Jinghui Li (Journal of Molecular Histology, 2026)

Parameter Interplays and Inverse Exploration in Centerless Grinding with Cup Wheel of Slender Ceramic Tubes - Jingguo Zhou; Bin Lin; Pengcheng Zhao; Jinming Li; Xingwang Xu; Cong Chen; Tianyi Sui (Rock Mechanics and Rock Engineering, 2026)

Realizing an evaporation rate of 4.31 kg·m−2·h−1 and an energy efficiency of 97.88% by assembling efficient mass transfer channels and full-spectrum solar-absorbing semiconductors into Janus evaporators - Haoquan Zhuang; Pengcheng Lin; Ying Chen (Chemical Engineering Journal, 2026)

Bacillus subtilis modulates the intestinal microbiome and metabolism to promote growth and disease resistance in Micropterus salmoides - Meiyu Li; Wengen Zhu; Shuhui Niu; Xingxing An; Lin Chen; Houxiong He; Yaohua Wang; Song Zhang; Yong Yang; Qirui Li; Huanping Liu; Shuhan Zhang; et al. (Aquaculture, 2026)

Microwave-induced phase transformation and ultrasound-driven interface reaction for Cu/Te separation - Renkun Luo; Zhonghua Li; Zhuoyu Yin; Shixing Wang; Hongliang Liu; Jiangcheng Wang; Pengcheng Zhang; Yonggang Zuo; Gengwei Zhang; Guo Lin; Libo Zhang; Likang Fu (Journal of Environmental Chemical Engineering, 2026)

Performance evaluation and mechanism analysis of different ice particle distribution shape parameter schemes in BCC-AGCM - Pengcheng Lin; Chunsong Lu; Yiming Liu; Xin He; Junjun Li; Tongwen Wu; Yixiong Lu (Atmospheric Research, 2026)

Faulting structure and seismic hazard: Insights from the 2024 MW 5.2 Bakersfield earthquake sequence - Weidong Li; Pengcheng Zhou; Fan Zhang; Jiangyang Zhang; Zhiyuan Zhou; Tao Zhang; Jinyu Tian; Jian Lin (Tectonophysics, 2026)

PCGF1 is a key factor for facilitating dynamic H3K27me3 modification during early lineage specification - Pan Chen; Xuejie Yang; Ruhai Chen; Hanlu Li; Jingwen Ma; Jing Chang; Guangliang Hong; Wei Liu; Xiongzhi Quan; Bin Yin; Lin Hou; Boqin Qiang; et al. (Science Bulletin, 2026)

Investigation of provincial clustering and spatial differences: Insights from the CO2 of China’s energy industry - Zhiqun Zhang; Haiying Liu; Yan Lin; Xianzhe Cai; Pengcheng Han; Dianwu Wang (Environment, Development and Sustainability, 2026)

Smoldering Combustion-Based calorimeter integrated with Dual-GRU network for online coal Quality analysis - Xuegang Zhang; Haiyuan Fu; Zhiming Lin; Qiwen Jin; Pengcheng Jiang; Xuecheng Wu (Fuel, 2026)

A three-dimensional reduced-order analysis method for flow and heat transfer performance of PCHE based on Bayesian optimization GPR model - Haowei Lin; Ziyan Zhao; Congyi Wen; Wei Li; Zijing Liu; Pengcheng Zhao (Annals of Nuclear Energy, 2026)

Pollutant control and material conversion of the waste graphite recovered from spent lithium-ion batteries: Preparation of building composite materials - Yusen Wu; Pengcheng Wang; Keyi Lin; Jiaqi Hu; Yonggao Fu; Jie Zhu; Jujun Ruan (Resources, Conservation and Recycling, 2026)

Controllable synthesis of organic phosphonic acids functionalized Ti3C2Tx for enhanced and selective uranium extraction - Siyi Wang; Pengcheng Zhang; Ziyang Wang; Xiangjian Meng; Yu Zang; Fei Wu; Lin Wang; Weiqun Shi; Suwen Chen (Chemical Engineering Journal, 2026)

Multiscale evolutionary morphologies and driving mechanisms of construction space in the China-Vietnam transnational border region - Pengcheng Wang; Rucheng Lu; Yuan Deng; Shugao Lin; Yiyun Li (Advances in Space Research, 2026)

Obstacles and bottleneck breakthroughs affecting the development of hydroxyl radicals assisted chemical mechanical polishing - Xingwang Xu; Bin Lin; Haopeng Chen; Bingrui Lv; Jinming Li; Pengcheng Zhao; Jingguo Zhou; Junqing Jia; Tianyi Sui; Jieqiong Lin (Journal of Environmental Chemical Engineering, 2025)

Portable point-of-care testing of food glutathione enabled by a high-performance sulfur-vacancy FeS mimetic enzyme - Zhen Huang; Lu Luo; Pengcheng Lin; Donglin Cao; Wei Xiao (Food Chemistry, 2025)

Overcoming the 4.55 V bottleneck in commercial LiCoO2: Synergistic interfacial pinning and coating via scalable processing - Caifang Qiu; Guiying Zhao; Zhiyang Zhang; Houlin Cheng; Youzu Xu; Pengcheng Wang; Yingbin Lin; Zhigao Huang; Jiaxin Li (Chemical Engineering Journal, 2025)

Lithospheric structure and geodynamics of oceanic transform fault - Fan Zhang; Jian Lin; Sanzhong Li; Yanhui Suo; Pengcheng Zhou; Yiming Luo; Caicai Zha; Xubo Zhang (Science China Earth Sciences, 2025)

Efficient utilization of energy enabled by form stable brine phase change cold storage gels with ultra-high latent heat towards green, safe and cost-effective fruit cold chain - Shiya Lin; Yiqi Xie; Xianyang Chen; Pengcheng Lin; Ying Chen (International Journal of Refrigeration, 2025)

Synergistic enhancement of solar interface evaporation by oxidation engineering of photothermal materials, hybridization of water channels and energy supplement of waterwheel - Yimeng Du; Jian Li; Mingfu Zhu; Pengcheng Lin; Ying Chen (Chemical Engineering Journal, 2025)

Interfacial depassivation enables long-cycling silicon-based solid-state batteries without stack pressure - Lu Zhao; Junwei Han; Xin Qin; Qian Xu; Fei Yang; Junshu Sun; Pengcheng Dai; Lin Shi; Debin Kong; Linjie Zhi (Chemical Engineering Journal, 2025)

The combined effects of convective entrainment and orographic drag on precipitation over the Tibetan Plateau - Junjun Li; Chunsong Lu; Jinghua Chen; Xu Zhou; Kun Yang; Xiaoqi Xu; Xianghua Wu; Lei Zhu; Xin He; Shiying Wu; Pengcheng Lin (Science China Earth Sciences, 2025)

Structural analysis and numerical modeling of multi-stage tectonic deformation in the Ziliujing anticline, SW Sichuan Basin, China: Implications for deformation propagation in salt-bearing fold-and-thrust belts - Jiawei Liu; Gang Rao; Sen Bai; Xiaolin Xiong; Jinwu Zhang; Wenxiong Yang; Chao Yin; Yaqi Zhong; Pengcheng Tang; Jianhua Qiu; Lin Gao (Tectonophysics, 2025)

The E3 ubiquitin ligase RNF182 regulates the induction of innate immune response against GCRV by mediating the ubiquitination of RIG-I in grass carp (Ctenopharyngodon idella) and rare minnow (Gobiocypris rarus) - Yusheng Lin; Haohao Feng; Yuxuan Wang; Shuai Liu; Pengcheng Hu; Jing Wang; Hong Cao (Fish & Shellfish Immunology, 2025)

Combining metabolomics to analyze the effects of cell wall component and stone cells on fruit texture in Dangshan pear - Pengcheng Wei; Xianang Wu; Xiaofeng Feng; Ping Lu; Yongping Cai; Lianping Wei; Lin Liu (Horticulture, Environment, and Biotechnology, 2025)

Skin-printable, anti-freezing, and recyclable ionic hydrogel bioelectrode for continuous electrophysiological monitoring - Meiqiong Zheng; Leqi Li; Xinyuan Ye; Zichong Ji; Yuli Wang; Zonglei Wang; Shihong Lin; Mingzhe Wang; Wenqing Yan; Jiawei Yang; Pengcheng Zhou; Yujie Zhang; et al. (Chemical Engineering Journal, 2025)

Regional differences and formation mechanisms of watershed territorial space patterns evolution: A case study of the critical areas in the Pearl River Basin - Shugao Lin; Pengcheng Wang; Peixin Zhu; Ke Huang; Rucheng Lu (Journal of Geographical Sciences, 2025)

Multisite synergistic interaction induced selective adsorption of CB5-Ti3C2T2 complex for strontium ion: A combined theoretical and experimental study - Sifan Li; Pengcheng Zhang; Yujuan Zhang; Kaikai Qiu; Lin Wang; Jianhui Lan; Yu Zhang; Xuwen Zhao; Chengzhen Miao; Weiqun Shi (Journal of Hazardous Materials, 2025)

A review: Integration of NIRS and chemometric methods for tea quality control-principles, spectral preprocessing methods, machine learning algorithms, research progress, and future directions - Shengpeng Wang; Clemens Altaner; Lin Feng; Panpan Liu; Zhiyu Song; Luqing Li; Anhui Gui; Xueping Wang; Jingming Ning; Pengcheng Zheng (Food Research International, 2025)

Effect of cultivar and process on the astringency of matcha based on flavonoids-targeted metabolomic analysis - Jinjin Xue; Panpan Liu; Yongquan Xu; Anhui Gui; Xueping Wang; Fei Ye; Lin Feng; Shengpeng Wang; Jing Teng; Shiwei Gao; Pengcheng Zheng (Food Research International, 2025)

DTD1 modulates synaptic efficacy by maintaining D-serine and D-aspartate homeostasis - Xiao Liu; Chaojuan Yang; Zhuoran Lin; Jianing Li; Bin Yin; Xuepei Lei; Wei Han; Boqin Qiang; Pengcheng Shu; Chen Zhang; Xiaozhong Peng (Science China Life Sciences, 2025)

Solar interfacial evaporation hydrogel with distributed packaging of phase change materials for continuous desalination - Qian Chen; He Zhang; Lie Zou; Rui Yang; Guangyong Zeng; Pengcheng Lin; Liu Yang; Mingming Zheng; Xiaoke Li (Chemical Engineering Journal, 2025)

A novel acid-free combined technology to achieve the full recovery of crystalline silicon photovoltaic waste - Mi Lin; Pengcheng Wang; Baojia Qin; Jujun Ruan (Waste Management, 2024)

Genetic diversity, antibiotic resistance, and pathogenicity of Aeromonas veronii isolated from farmed largemouth bass (Micropterus salmoides) in the main aquaculture regions of China - Qikai Chen; Yunfei Xing; Yan Lei; Guixiang Tong; Xiaobu Lin; Pengcheng He; Shaolin Tang; Feifei Zheng; Hui Zeng; Xinxian Wei; Yong-An Zhang; Yang Zhou (Aquaculture, 2024)

Magnetic bio-based Fe3O4@urushiol-Fe polymeric nanoparticles for efficient photothermal sterilization - Weibin Bai; Xu Zhang; Xinghang Chen; Pengcheng Li; Jinxin Huang; Jiani Chen; Shijing Zheng; Xiaoyan Li; Yucai Lin; Rongkun Jian (Journal of Environmental Chemical Engineering, 2024)

Enhancing interfacial compatibility and ionic transportation kinetics in lithium-rich manganese oxide via magnetron sputtering conformal coating with amorphous LiPON - Yue Chen; Yulin Huang; Chenxi Fang; Pengcheng Wang; Houlin Cheng; Guiying Zhao; Yingbin Lin; Zhigao Huang; Jiaxin Li (Chemical Engineering Journal, 2024)

Long-term mulched drip irrigation enhances the stability of soil aggregates by increasing organic carbon stock and reducing salinity - Mingdong Tan; Wenhao Li; Rui Zong; Xuanzhi Li; Yue Han; Pengcheng Luo; Yam Prasad Dhital; Haixia Lin; Haiqiang Li; Zhenhua Wang (Soil and Tillage Research, 2024)

Clean water harvesting and power generation by solar-absorbing Germanium@k-carrageenan evaporator demonstrating superior energy conversion - Yingying Chen; Lifang Chen; Zhi Yang; Wenhao Wang; Pengcheng Lin; Bing Yao (Journal of Cleaner Production, 2024)

Design and application of Cd2+ polypeptide fluorescent probes based on Aggregation Induced Emission (AIE) - Jiang Zhou; Xuejiao Wang; Dajiang Wang; Liangchao Yuan; Junlei Hao; Jingcheng Hou; Jiang Wu; Pengcheng Lin (Journal of Molecular Histology, 2024)

Unlocking the secrets of Qingzhuan tea: A comprehensive overview of processing, flavor characteristics, and health benefits - Panpan Liu; Lin Feng; Jia Chen; Shengpeng Wang; Xueping Wang; Yanna Han; Mengjun Ma; Zhonghua Liu; Pengcheng Zheng (Trends in Food Science & Technology, 2024)

Molten salt synthesis of MXene-derived hierarchical titanate for effective strontium removal - Siyi Wang; Pengcheng Zhang; Enzhao Ma; Suwen Chen; Zijie Li; Liyong Yuan; Jianhua Zu; Lin Wang; Weiqun Shi (Journal of Hazardous Materials, 2024)

Hierarchical nanocomposites of redox covalent organic frameworks nanowires anchored on graphene sheets for super stability supercapacitor - Daping Hu; Yuhang Jia; Shaopei Yang; Changqing Lin; Fuyao Huang; Runhai Wu; Shimeng Guo; Kefeng Xie; Pengcheng Du (Chemical Engineering Journal, 2024)

One-pot eutectic molten salt synthesis of MXene-supported nanoscale zero-valent iron composites for efficient adsorption and reduction of uranium - HaoWei Tu; YanZe Wu; ZiJie Li; PengCheng Zhang; Cuilian Wei; LiYong Yuan; NanNan Wang; Lin Wang; WeiQun Shi (Chemical Engineering Journal, 2024)

Age, Growth, and Reproductive Biology of Euchiloglanis davidi in the Middle and Lower Yalong River, China - Jie Chen; Xiangyun Zhu; Xin Yang; Xianqin Hu; Pengcheng Lin; Bin Xu; Kaijin Wei; Baoshan Ma (Fishes, 2023)
In the present study, we investigated the age, growth, and reproductive characteristics of Euchiloglanis davidi, a species of Sisoridae fishes, from the Yalong River, China. Fish samples were collected from the tributaries of the middle and lower Yalong River in May 2013 and December 2015. Their standard length ranged from 67 to 190 mm, and the total weight ranged from 3.42 to 75.06 g. The age and growth pattern of E. davidi were determined using the vertebra. Furthermore, the sampled fish were categorized into 10 age groups (1–10 years old): the maximum age was 10 years and 9 years for male and female fish, respectively. The relationship between the standard length and weight was expressed as W = 6.744 × 10−5 L2.653, and the t-test showed allometric growth. The growth of E. davidi was defined by the von Bertalanffy growth function, described as Lt = 260.8(1−e−0.104(t+1.942)), Wt = 173.5(1−e−0.104(t+1.942))2.653, respectively. The growth inflection point was observed at 7.44 years, with corresponding length and weight values of 162.50 mm and 49.46 g. The fecundity ranged from 105 to 352 eggs, with an average of 205 eggs. The relative fecundity of weight (FW) ranged from 2.90 to 8.98 eggs/g, and the relative fecundity of length (FL) ranged from 0.71 to 2.11 eggs/mm. Altogether, these characteristics of slow growth and low fecundity demonstrated the vulnerability of E. davidi to exploitation in the middle and lower reaches of the Yalong River.

Novel cationic porous materials with open architectures for highly efficient palladium recovery: Integrated experimental studies and DFT simulations - Pengcheng Wu; Yongjie Jiang; Wenxia Lin; Ke Wang; Kexin Wang; Song Qin; Yimin Cai; Lihua Yuan; Wen Feng (Hydrometallurgy, 2023)

Numerical examination of the geomorphic indicators for lateral fold growth - Lin Gao; Chuanqi He; Gang Rao; Ci-Jian Yang; Xiaoping Yuan; Jingtao Lai; Pengcheng Tang; Lei Wu (Geomorphology, 2023)

Dynamic Process Study of Earthquake-Induced Landslides Applying an Improved Discontinuous Deformation Analysis Method Considering Site Response - Jinmei Wang; Yingbin Zhang; Pengcheng Yu; Bo Shu; Qingdong Wang; Yong Xu; Lin Lang; Xinyan Peng (Rock Mechanics and Rock Engineering, 2023)

Transcriptional repressor AGL79 positively regulates flowering time in Arabidopsis - Haibo Yang; Pengcheng Zhang; Diandian Guo; Na Wang; Hao Lin; Xingchun Wang; Lifang Niu (Journal of Plant Physiology, 2023)

A portable high-performance self-insulated solar evaporator based on wooden sponge for seawater desalination and wastewater purification - Xi Zhao; Yingying Chen; Pengcheng Lin; Hua Su; Ying Chen (Desalination, 2023)

Crowding-out strategy to enhance energetics of 3-nitro-1,2,4-triazol-5-one based E-MOFs at the molecular level through adjusting pH - Xiaopeng Zhang; Tianyang Hou; Yige Wu; Ze Xu; Qiuhan Lin; Pengcheng Wang; Yuangang Xu; Ming Lu (Chemical Engineering Journal, 2023)

Remediation performance and mechanisms of Cu and Cd contaminated water and soil using Mn/Al-layered double oxide-loaded biochar - Pengcheng Lin; Hang Liu; Hua Yin; Minghan Zhu; Haoyu Luo; Zhi Dang (Journal of Environmental Sciences, 2023)

Reproductive Characteristics of Pseudecheneis sulcatus (Siluriforms: Sisoridae) in the Lower Yarlung Zangbo River, Tibet - Pengcheng Lin; Huaming Hu; Zheng Gong; Jian Wang; Xin Gao (Fishes, 2023)
The present research offers novel understandings of the reproductive biology of Pseudecheneis sulcatus (McClelland, 1842) found in the Yarlung Zangbo Grand Canyon, a biodiversity hotspot. Reproductive characteristics of Pseudecheneis sulcatus, including their maturation age, fertility, spawning season, and maximum body size, constitute important aspects of its life-history traits. We collected a total of 310 specimens from the Yarlung Zangbo River’s Motuo reach between March and November 2016 and found the male-to-female ratio to be 0.73:1, markedly different from the anticipated 1:1. The total length of individuals ranged from 72 to 207 mm, while overall weight ranged from 2.5 to 65.0 g. Their length at first maturity was estimated as 131 mm in males and 132 mm in females. Based on the adult proportion and fluctuation in the monthly gonadosomatic index (GSI) and size distribution of oocytes, spawning was determined to occur from March to June. The absolute fecundity ranged between 247 and 2886 eggs, while the fluctuation in average relative fertility ranged between 16.8 and 77.1 eggs/g of fish. The fecundity of P. sulcatus was linearly correlated to the overall weight and length of the fish along with the ovarian weight. In conclusion, P. sulcatus spawned synchronously in spring and early summer, exhibiting low fecundity and large oocytes. Our results provided basic information in understanding how this species adapted well to the unique canyon environment, which may be useful for developing a sustainable conservation plan for P. sulcatus at the lower reach of the Yarlung Zangbo River.

Self-repairing thermal energy storage gels demonstrating superior thermophysical properties and wearability towards personal thermal management in static and dynamic modes - Yingying Luo; Hongjiao Wu; Junpeng Qiao; Jiaming Zhang; Kai Liu; Liqing Zou; Ying Chen; Pengcheng Lin (Chemical Engineering Journal, 2023)

4,4′-Bis(trinitromethyl)-3,3′-azo/azoxy-furazan: High-energy dense oxidizers - Shuaiqi Wang; Yuangang Xu; Shuaijie Jiang; Feng Yang; Dongxue Li; Pengcheng Wang; Qiuhan Lin; Ming Lu (Chemical Engineering Journal, 2023)

Effect of Rigid Vegetation Arrangement on the Mixed Layer of Curved Channel Flow - Tianwei Huang; Mengxing He; Kan Hong; Yingtien Lin; Pengcheng Jiao (Journal of Marine Science and Engineering, 2023)
Curved channels and aquatic vegetation are commonly present in the riverine environment. In this study, the effects of vegetation density and distribution on the hydrodynamic characteristics of a mixed layer developed over a 180-degree curved channel were investigated through flume experiments. Wooden sticks were used to simulate rigid vegetation distributed along the half side of the channel, and a 200 Hz acoustic Doppler velocimeter (ADV) was employed to measure the three-dimensional instantaneous velocity at five selected cross sections along the curved channel. Experimental results show that the vegetation covering the half of the channel significantly affects the hydrodynamic structure of the curved channel flow, and the unequal vegetation resistance induces the K-H instability at the vegetation and non-vegetation interface, resulting in a standard hyperbolic tangent function of streamwise velocity distribution along the lateral direction. The influence of curve position on turbulence kinetic energy is far greater than that of vegetation density and vegetation distribution. The peak value of turbulent kinetic energy is comprehensively affected by vegetation density and distribution, and the peak position of turbulent kinetic energy at the interface is changed by different vegetation distribution. The combined effect of the curve and the partly covered vegetation increases the mixing between the water bodies, enhancing turbulent kinetic energy, and vegetation along the concave bank plays a more significant role. For turbulent bursting, the inward and outward interactions are mainly bursting events in the vegetation area, while ejections and sweeps are dominant in the non-vegetation area. However, the critical vegetation condition to initiate large-scale coherent structure (LSS) in the mixed layer and the influence of flexible vegetation need to be further studied in the future.

Regulation mechanism of cyanide production and conversion of Pseudomonas fluorescens commonly used in bio-cyanidation of precious metals from waste printed circuit boards - Mi Lin; Zichun Yao; Pengcheng Wang; Yonggao Fu; Jujun Ruan (Resources, Conservation and Recycling, 2023)

Analysis of Timing Effect on Flow Field and Pulsation in Vertical Axial Flow Pump - Fan Yang; Pengcheng Chang; Yao Yuan; Na Li; Rongsheng Xie; Xiaowen Zhang; Zhikang Lin (Journal of Marine Science and Engineering, 2021)
Vertical axial flow pump device has the characteristics of large flow and low head, which is widely used in pumping station projects with head of 3–9 m. In order to study the influence of the timing effect of the impeller relative flow channel and guide vane on the flow field and pulsation in the axial flow pump device, the whole flow channel of the vertical axial flow pump device was taken as the research object. The reliability of the numerical simulation was verified by physical model test. The flow field characteristics and pressure pulsation characteristics of the inlet and outlet regions of the impeller, the guide vane and the campaniform inlet conduit at different timing positions of the impeller under different flow rates were analyzed. The results show that the pressure coefficient distribution of the impeller inlet of the vertical axial flow pump device presents four high-pressure areas and four low-pressure areas with the rotation of the impeller. The pressure pulsation at the inlet and outlet of the impeller is mainly affected by the rotation of the impeller, and the main frequency is 4 times the rotation frequency amplitude of pressure pulsation decreases with the increase of flow rate. When the flow rate increased from 0.8 Qbep to 1.2 Qbep, the average velocity circulation at the guide vane outlet decreased by 12%; there is an obvious negative value region of the internal regularized helicity of the guide vane. When the flow rate increases from 0.8 Qbep to 1.2 Qbep, the amplitude of the pressure pulsation coefficient at the outlet of the guide vane decreases gradually, with a decrease of 94%. When the flow rate is 1.2 Qbep, the main frequency and the secondary frequency of the pressure pulsation are both low-frequency, with obvious low-frequency pulsation characteristics. Under the small flow condition of 0.8 Qbep, the outlet flow fluctuation of seven guide vane was 18.9% on average, and the flow variation of each guide vane was large. Under the optimal flow condition of 1.0 Qbep and large flow condition of 1.2 Qbep, the outlet flow fluctuation of 7 guide vane is 4.7% and 0.56% on average, and the flow change of each guide vane is stable. The outlet flow of the guide vane is mainly concentrated in two guide vane slots of the guide vane, and the flow ratios are 30.56%, 30.14% and 29.16% under three flow conditions, respectively. The research results provide a scientific basis for the optimization design and stable operation of vertical axial flow pump device.

MicroRNA-9 facilitates hypoxia-induced injury and apoptosis in H9c2 cells via targeting CDK8 - Pengcheng Dou; Guangshuang Tan; Zhihua Fan; Jiatong Xiao; Chaoran Shi; Zhengjun Lin; Juan Duan (Journal of Biosciences, 2021)

Optimizing the Wheat Seeding Rate for Wide-Space Sowing to Improve Yield and Water and Nitrogen Utilization - Zhixin Wang; Shahbaz Khan; Min Sun; Aixia Ren; Wen Lin; Pengcheng Ding; Hafeez Noor; Shaobo Yu; Yu Feng; Qiang Wang; Zhiqiang Gao (International Journal of Plant Production, 2021)

Reproductive characteristics of Psilorhynchus homaloptera Hora and Mukerji, 1935 (Cyprinidae: Psilorhynchidae) in the lower Yarlung Zangbo River, Tibet - Pengcheng Lin; Huaming Hu; Fei Liu; Mingzheng Li; Huanzhang Liu (Journal of Oceanology and Limnology, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Shallow unloading deformation analysis on Baihetan super-high arch dam foundation - Peng Lin; Jie Shi; Pengcheng Wei; Qixiang Fan; Zhilin Wang (Bulletin of Engineering Geology and the Environment, 2019)

Long non-coding RNA RP11-6O2.4 indicates poor prognosis and suppresses cell cycle progression through the p38-MAPK signaling pathway in gastric cancer - Yang Feng; Zhiming Fu; Yajun Luo; Wang Tan; Zilin Liu; Pengcheng Ye; Fei Lu; Wanping Xiang; Linghan Tang; Lin Yao; Mengyun Song; Qingmei Huang; et al. (Molecular & Cellular Toxicology, 2019)

Long-term monitoring revealed fish assemblage zonation in the Three Gorges Reservoir - Pengcheng Lin; Xin Gao; Fei Liu; Mingzheng Li; Huanzhang Liu (Journal of Oceanology and Limnology, 2019)

Reinforcement Analysis of Toe Blocks and Anchor Cables at the Xiluodu Super-High Arch Dam - Jie Shi; Peng Lin; Yuande Zhou; Pengcheng Wei; Renkun Wang (Rock Mechanics and Rock Engineering, 2018)

Logistic model-based genetic analysis for kernel filling in a maize RIL population - Shuangyi Yin; Pengcheng Li; Yang Xu; Lin Xue; Derong Hao; Jun Liu; Tiantian Yang; Zefeng Yang; Chenwu Xu (Euphytica, 2018)

Jasmonic acid involves in grape fruit ripening and resistant against Botrytis cinerea - Haifeng Jia; Cheng Zhang; Tariq Pervaiz; Pengcheng Zhao; Zhongjie Liu; Baoju Wang; Chen Wang; Lin Zhang; Jinggui Fang; Jianpu Qian (Functional & Integrative Genomics, 2016)

Soluble Epoxide Hydrolase Deficiency or Inhibition Attenuates MPTP-Induced Parkinsonism - Xiaocui Qin; Qiaoqi Wu; Lifang Lin; Aimin Sun; Shuhu Liu; Xiaowen Li; Xiong Cao; Tianming Gao; Pengcheng Luo; Xinhong Zhu; Xuemin Wang (Molecular Neurobiology, 2015)

Development and characterization of polymorphic microsatellite marker for Dactylorhiza hatagirea (D. Don) Soo - Pengcheng Lin; Liyan Zeng; Zhen Yang; Ruike Liu; Yang Zhong (Conservation Genetics Resources, 2014)